Investigation of Malaysian higher education quality culture and workforce performance - Mohd Ali, Hairuddin; Musah, Mohammed Borhandden (Emerald, 2012)
Purpose – The purpose of this study is to examine the relationship between the quality culture and workforce performance in the Malaysian higher education sector. The study also aims to test and validate the psychometric properties of the quality culture and workforce performance instruments used in the study.